Cover Feature: Fe3O4/g‐C3N4 Nanozyme for Production of L‐DOPA as Mimetics of Tyrosine Hydroxylase (ChemNanoMat 2/2023). Issue 2 (23rd January 2023) - Shang, Qi; Zhang, Ling; Chen, Chan; Tang, Weikang; Han, Mengqi; Chen, Qinfei; Liu, Wenbin
Abstract : A nanozyme was developed for biomimetic synthesis of L‐DOPA by mimicking natural tyrosine hydroxylase. Fe3 O4 /g‐C3 N4 nanocomposite performed as a nanozyme with close resemblance in structure, activity, and mechanism to tyrosine hydroxylase. Fe atoms coordinated with N atom in g‐C3 N4 nanosheet served as the active site of the nanozyme. The nanozyme catalyzed selective hydroxylation of tyrosine to L‐DOPA in the presence of visible light irradiation and hydrogen peroxide. The nanozyme shared an identical catalytic mechanism with tyrosine hydroxylase from the aspect of involvement of Fe IV O 2+ . More information can be found in the Research Article by Wenbin Liu et al.